Motion‐robust sub‐millimeter isotropic diffusion imaging through motion corrected generalized slice dithered enhanced resolution (MC‐gSlider) acquisition. Issue 5 (1st April 2018) - Wang, Fuyixue; Bilgic, Berkin; Dong, Zijing; Manhard, Mary Kate; Ohringer, Ned; Zhao, Bo; Haskell, Melissa; Cauley, Stephen F.; Fan, Qiuyun; Witzel, Thomas; Adalsteinsson, Elfar; Wald, Lawrence L.; et al.
Abstract : Purpose: To develop an efficient MR technique for ultra‐high resolution diffusion MRI (dMRI) in the presence of motion. Methods: gSlider is an SNR‐efficient high‐resolution dMRI acquisition technique. However, subject motion is inevitable during a prolonged scan for high spatial resolution, leading to potential image artifacts and blurring. In this study, an integrated technique termed Motion Corrected gSlider (MC‐gSlider) is proposed to obtain high‐quality, high‐resolution dMRI in the presence of large in‐plane and through‐plane motion. A motion‐aware reconstruction with spatially adaptive regularization is developed to optimize the conditioning of the image reconstruction under difficult through‐plane motion cases. In addition, an approach for intra‐volume motion estimation and correction is proposed to achieve motion correction at high temporal resolution. Results: Theoretical SNR and resolution analysis validated the efficiency of MC‐gSlider with regularization, and aided in selection of reconstruction parameters. Simulations and in vivo experiments further demonstrated the ability of MC‐gSlider to mitigate motion artifacts and recover detailed brain structures for dMRI at 860 μm isotropic resolution in the presence of motion with various ranges. Conclusion: MC‐gSlider provides motion‐robust, high‐resolution dMRI with a temporal motion correction sensitivity of 2 s, allowing for the recovery of fine detailed brain structures in the presence of large subject movements.